2018
DOI: 10.5194/acp-18-17087-2018
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the large-scale electrification equilibrium effects in dust storms using field observations at Qingtu Lake Observatory

Abstract: Abstract. Dust and sand electrification, which is a ubiquitous phenomenon in dust events, has a potentially dramatic effect on dust and sand lifting and transport processes. However, the effect of such electrification is still largely unclear, mainly due to its complexity and sparse observations. Here, we conducted an extensive observational analysis involving mild and severe dust storms with minimum visibility, ranging from ∼0.09 to 0.93 km, to assess the electrical properties of airborne dust particles in du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…2(a) and compared with that extracted by moving average and adaptive wavelet transform. The results show that the timevarying average velocities extracted by different methods are basically consistent and that extracted by EMD can better reflect the time-varying characteristics (confirmed by Zhang and Zheng, 2018), the correlation coefficient between the corresponding fluctuating velocities after removing the mean is larger than 0.93.…”
Section: Data Preprocessingmentioning
confidence: 55%
“…2(a) and compared with that extracted by moving average and adaptive wavelet transform. The results show that the timevarying average velocities extracted by different methods are basically consistent and that extracted by EMD can better reflect the time-varying characteristics (confirmed by Zhang and Zheng, 2018), the correlation coefficient between the corresponding fluctuating velocities after removing the mean is larger than 0.93.…”
Section: Data Preprocessingmentioning
confidence: 55%
“…For example, Jackson and Farrell (2006) recorded the horizontal component of the E-field of up to 120 kV m -1 in dust devils. Zhang and Zheng (2018) also found the streamwise and spanwise components (termed horizontal component) of the E-field of up to 150 kV m -1 in dust storms. Hence, E-field is actually three-dimensional (3-D).…”
Section: Introductionmentioning
confidence: 79%
“…It is worth noting that the measured time series in dust storms are generally non-stationary when viewed as a whole (e.g. Zhang and Zheng, 2018). In such cases, the statistical values are timevarying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent results show that such contained considerable energy structures were also existed and increased with heights (Hutchins et al, 2012;Wang and Zheng, 2016). Notably, Zhang and Zheng (2018) found that the space charge density and dust concentration were significantly correlated over the 10-min timescales. Therefore, the complex mechanic system during the SDS raises a great interest to investigate what kind of structures will exist and how the structures will be evolved.…”
mentioning
confidence: 97%